Pewarnaan Titik Ketakteraturan Lokal pada Keluarga Graf Unicyclic - Khilyah Munawaroh; Arika Indah Kristiana; Ermita Rizki Albirri; Dafik Dafik; Robiatul Adawiyah (jcgant, 2021)
In this research is a development of local irregularity vertex coloring of graph. The based on definition, as follows: l:V(G) {1, 2, ..., k} is called vertex irregular k-labelling and w:V(G) N where w(u) = _ v N(u)l(v), w is called local irregularity vertex coloring. A condition for w to be a local irregularity vertex coloring, If opt(l) = min{maks(li); li, vertex labelling function, and for every u,vE(G),w(u)w(v). The chromatic number local irregularity vertex coloring is denoted by χ_lis(G). In this paper, the researchers will discuss of local irregularity vertex coloring of related unicyclic graphs and we have found the exact value of their chromatic number local irregularity, namely cricket graph, net graph, tadpole graph, peach graph, and bull graph.",